TRANSFORMASI MAKNA PANCASILA DARI ORDE LAMA KE REFORMASI: STUDI WACANA IDEOLOGI NEGARA - Try Widya Andini; Naina Ikhdina Hapiz; Qesya Balqis Lubis; Zaskia Putri Andari; Shintya Akrima; Sri Yunita (STKIP Subang, 2026)
Pancasila as the state ideology of Indonesia possesses a dynamic character, with its meaning continuously transforming in response to changing historical, political, and social contexts. This study aims to analyze the shifts in the meaning of Pancasila across different periods of governance in Indonesia. The research employs a qualitative approach using critical discourse analysis through a literature review. The findings indicate that during the early period of independence, Pancasila functioned as a common platform for national integration. During the Old Order and New Order eras, Pancasila underwent ideological consolidation and was utilized as an instrument of political legitimacy and control through a predominantly singular interpretation. In contrast, the Reform Era repositions Pancasila as an open ideology that allows for a plurality of interpretations, although its implementation continues to face various challenges. This study affirms that Pancasila is an ideological construct that is continuously negotiated within the interplay of language, power, and social practices.